Wogan's Ireland : A Tour Around the Country that Made the Man - Wogan, Terry; edited by Lawrence, Francine (London Simon & Schuster, 2011)
"Fully illustrated throughout with photos of stunning Irish scenery, Terry Wogan takes a revelatory tour back to his native Ireland in this gorgeous and thought provoking photographic journey In a magical mix of the personal and the political, the humorous and the tragic, the historic and the modern, this book photographically follows Terry Wogan on a return to his native land. Terry left Ireland in the late 1960s, after a childhood in Limerick dominated by the Catholic Church. Here, we see through Terry's eyes how the country has changed since then. He rediscovers its rugged coastline and the spectacular views he remembers from childhood holidays. He revisits old haunts, and hooks up with long-lost friends, colleagues, and fellow ex-pats, enjoying the nostalgia evoked by these experiences. But he doesn't shy away from the more complicated responses that led him to seek his fortunes elsewhere, as he also explains during the course of the book why he had to leave it all behind. The series will reflect the man himself: witty and urbane, relaxed yet engaging. But it will also reveal an unfamiliar Wogan$1 (Bpassionate, serious, investigative, and sometimes very emotional."--Publisher description.s
Include Colored Illustration, Indexes
Keywords: Travel -- Ireland -- Wogan, Terry